Relative Leukocyte Telomere Length and Genetic Variants in Telomere-Related Genes and Serum Levels Role in Age-Related Macular Degeneration - Alvita Vilkeviciute; Greta Gedvilaite; Mantas Banevicius; Loresa Kriauciuniene; Dalia Zaliuniene; Olivija Dobiliene; Rasa Liutkeviciene (Cells, 2022)
Telomere shortening is well known to be associated with ageing. Age is the most decisive risk factor for age-related macular degeneration (AMD) development. The older the individual, the higher the AMD risk. For this reason, we aimed to find any associations between telomere length, distribution of genetic variants in telomere-related genes (TERT, TERT-CLPTM1, TRF1, TRF2, and TNKS2), and serum TERF-1 and TERF2 levels on AMD development. Methods: Our study enrolled 342 patients with AMD and 177 healthy controls. Samples of DNA from peripheral blood leukocytes were extracted by DNA salting-out method. The genotyping of TERT rs2736098, rs401681 in TERT-CLPTM1 locus, TRF1 rs1545827, rs10107605, TNKS2 rs10509637, rs10509639, and TRF2 rs251796 and relative leukocyte telomere length (T/S) measurement were carried out using the real-time polymerase chain reaction method. Serum TERF-1 and TERF2 levels were measured by enzymatic immunoassay (ELISA). Results: We found longer telomeres in early AMD patients compared to the control group. Additionally, we revealed that minor allele C at TRF1 rs10107605 was associated with decreases the odds of both early and exudative AMD. Each minor allele G at TRF2 rs251796 and TRF1 rs1545827 C/T genotype and C/T+T/T genotypes, compared to the C/C genotype, increases the odds of having shorter telomeres. Furthermore, we found elevated TERF1 serum levels in the early AMD group compared to the control group. Conclusions: In conclusion, these results suggest that relative leukocyte telomere length and genetic variants of TRF1 and TRF2 play a role in AMD development. Additionally, TERF1 is likely to be associated with early AMD.